Acoustic carrier transportation induced by surface acoustic waves in graphene in solution. (11th March 2016) - Okuda, Satoshi; Ikuta, Takashi; Kanai, Yasushi; Ono, Takao; Ogawa, Shinpei; Fujisawa, Daisuke; Shimatani, Masaaki; Inoue, Koichi; Maehashi, Kenzo; Matsumoto, Kazuhiko
Abstract: The acoustic charge transportation induced by surface acoustic wave (SAW) propagation in graphene in solution was investigated. The sign of acoustic current ( I A ) was found to switch when crossing the Dirac point because the major carrier was transitioned from holes to electrons by the change in electrolyte-gate voltage. I A also exhibited a peak value under conditions of both hole and electron conduction. These results can be explained on the basis of a change in the type of major carrier in graphene, as well as a change in the carrier mobility of graphene.